Pengaruh Sosial Budaya terhadap Pemberian Makanan Pendamping ASI (MPASI) Dini di Desa Bente Kecamatan Mandah Kabupaten Indragiri Hilir - Mia Rita Sari; Dewi Erlina Asrita Sari (Maternal & Neonatal Health Journal, 2022)
Giving Breast Milk Substitute (GBMS) before the child is 6 months old is not recommended because it can increase the risk of disease, especially diarrhea. In Bente Village, Mandah District, Indragiri Hilir Regency, the coverage of exclusive breastfeeding in 2019 was 30.2%. Socio-cultural factors are one of the factors that influence the provision of early breastfeeding complementary foods. On socio-cultural influences, as much as 70% of mothers give complementary foods to breast milk at the age of <4 months and assume the baby is still hungry if only breastfed. This study aims to determine the influence of socio-cultural on the provision of complementary early breastfeeding in Bente Village, Mandah District, Indragiri Hilir Regency. Research is analytic observational with a cross-sectional research design. The population is all mothers who have babies 0-24 months from January to March 2020 as many as 60 people, with a sample of 46 respondents and the sampling was done by accidental sampling. Data analysis was performed using the Chi-Square Test. The results showed that 67.4% of mothers gave complementary foods according to culture in the family/community, there was a socio-cultural influence on early breastfeeding with p-value 0.000. It is hoped that mothers will be more active in seeking information about complementary foods from health workers, mass media, electronic media or other sources so that they are not influenced by the culture of the surrounding environment in providing complementary foods to breast milk for babies.